The Effect of Production and Sales Costs on Net Profit of Micro, Small and Medium Business in Bulukumba District (Case Study of Marning Corn Production MSMEs) - Nasrullah; Andi Rustam; Sultan Sarda; Mutmainna; Irpan (www.amertainstitute.com, 2023)
The analysis techniques in this study are validity test, reliability test, classic assumption test, multiple linear regression analysis test and hypothesis testing through determination test and t (partial) test. The results of this study indicate that partially Production Costs have a positive and significant effect on Net Income (Study on Micro, Small and Medium Enterprises Cases in Bulukumba Regency) as indicated by a calculated T value of 3.498 > Table T value of 2.04523 and a significance value of 0.002 < 0. 05. Sales have a positive and significant effect on net income (Study on Micro, Small and Medium Enterprises in Bulukumba Regency) as indicated by a calculated T value of 2.692 > Table T value of 2.04523 and a significance value of 0.012 < 0.05.